Língua Portuguesa na Região Administrativa Especial de Macau: políticas e programas do ensino do português como língua estrangeira - Escaleira, Maria de Lurdes Nogueira (Linguarum Arena, 2018)
This paper aims to discuss the policies and practices of the Portuguese language teaching in Macau in the period following the handover, i.e., from the 20th December 1999 to the present. Thus, the focus of this research is the situation of teaching/learning Portuguese since the handover, with the objective of providing leads, so that researchers, especially from abroad, will have a set of information to support future research on this subject. A number of policies are reviewed, such as those establishing Portuguese as one of the official languages of the Special Administrative Region (SAR) of Macau, or others, supporting the language spread and teaching, with the objective of training “bilingual talents”3 which will allow Macau to turn into the Platform between China and the Portuguese-speaking countries. Current data indicates that there is an increase in demand for courses for Portuguese as a second language, caused, in our view, by the shift in paradigm in how the value of the Portuguese language is understood. Notwithstanding the reticence associated to how many would consider a language to have only an affective and cultural value, the fact is that, in Mainland China and in Macau, Portuguese draws students as it has an ever-greater economic weight. Indeed, the People’s Republic of China’s Central Government’s policy of economic openness to Portuguesespeaking countries has exponentially increased the demand for bilingual professionals, speaking Chinese and Portuguese, facilitating their integration into the work market, and leading to attractive wages. Chinese pragmatism leads to Portuguese language courses being regarded as the door to a promising future, even if, in a second phase, there is also an affective connection and the interest for the culture underlying the language. We may conclude that there are significant policies and practices, while there is lacking of a strategic management allowing a global vision and an interconnection/ coordination between the various levels of teaching, so that learning would become gradual and cumulative, avoiding the numerous “new starts” which take place due to ignoring the students’ history concerning Portuguese language learning.